Research Notes: The Antecedents and Consequences of Union Commitment: A Meta-Analysis - Bamberger, Peter; Kluger, Avraham N.; Suchard, Ronena (Academy of Management Journal, 1999)
We tested three published models of union commitment?s antecedents and consequences as well as an integrative model, using correlation coefficients derived from 15 meta-analyses of five union commitment correlates: prounion attitudes, union instrumentality, organizational commitment, job satisfaction, and union participation. The integrative model offered significantly better fit to the data than the other models, suggesting that the effects of job satisfaction and union instrumentality on union commitment are partially mediated by organizational commitment and union attitudes, respectively. Also, prounion attitudes had an effect on union commitment equal to, if not stronger than, that of union instrumentality.